Taste peptides derived from Stropharia rugosoannulata fermentation mycelium and molecular docking to the taste receptor T1R1/T1R3 - Li, Wen; Chen, Wanchao; Wu, Di; Zhang, Zhong; Yang, Yan (Frontiers in Nutrition, 2022)
This study identified the peptides in the fermentation mycelia of Stropharia rugosoannulata. The molecular weight of the peptides was below 3000 Da. Heptapeptides to decapeptides were the main peptides in the fermentation mycelia of S.rugosoannulata. More than 50% of the peptides had salty and umami taste characteristics, and the long-chain peptides (decapeptides to twenty-four peptides) also played an essential role in the pleasant taste characteristics of mycelium. In the salty and umami peptide of S.rugosoannulata, the distribution of non-polar hydrophobic amino acids and polar uncharged amino acids accounted for a relatively high proportion, and the proportion of polar uncharged amino acids further increased with the extension of the peptide chain. P, F, I, l, V, G, S, T, and D, are the amino acids with a high proportion in the peptides. The taste peptides can bind to more than 60% of the active amino acid residues in the cavity binding domain of the T1R1/T1R3 receptors. Hydrogen bond interaction was the primary mode of interaction between the peptides and the receptor. The first and second amino acid residues (such as S, V, E, K, G, and A) at the C-terminal and N-terminal of the peptides were easy to bind to T1R1/T1R3 receptors. Asp108, Asn150, Asp147, Glu301, Asp219, Asp243, Glu70, Asp218 in T1R1, and Glu45, Glu148, Glu301, Glu48, Ala46 in TIR3 were the key active amino acid sites of taste peptides binding to T1R1/T1R3 receptors.